2022
DOI: 10.1029/2022tc007348
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of the Mesozoic Succession of Franz Josef Land (North‐Eastern Barents Sea): Paleogeographic and Tectonic Implications for the High Arctic

Abstract: The Barents Sea sedimentary basin represents one of the key prospective regions for hydrocarbon resources in the Arctic realm (Figures 1a and 1b). However, while the Norwegian part of the Barents Sea is covered by a dense network of seismic lines and penetrated by numerous wells, the Russian portion is comparatively poorly studied. To date, the sedimentary succession of the Russian part has only been penetrated by a few wells drilled in the southern part of the basin and four wells drilled onshore across the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 82 publications
(220 reference statements)
0
9
0
Order By: Relevance
“…A previous provenance study of the Triassic-Cretaceous strata on FJL on the same samples was based on the U-Pb and (U-Th)/He dating of detrital zircons [36]. Detrital zircon U-Pb dating revealed that Triassic grains form a small peak at 220-230 Ma.…”
Section: Previous Provenance Studymentioning
confidence: 99%
See 3 more Smart Citations
“…A previous provenance study of the Triassic-Cretaceous strata on FJL on the same samples was based on the U-Pb and (U-Th)/He dating of detrital zircons [36]. Detrital zircon U-Pb dating revealed that Triassic grains form a small peak at 220-230 Ma.…”
Section: Previous Provenance Studymentioning
confidence: 99%
“…The Barents continental shelves supposedly comprise Neoproterozoic and Early-Middle Paleozoic basement domains [29][30][31][32]. The pre-Mesozoic stratigraphic framework of FJL is based on the stratigraphy penetrated by the deep Nagurskaya well, drilled on Alexandra Land Island in the westernmost part of the archipelago [33][34][35], along with a detailed studied of the conglomerates containing reworked clasts of older stratigraphy in the south-eastern part of FJL [36].…”
Section: Geological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…On the islands of Wilczek and Klagen‐Furth of Franz Josef Land archipelago, ammonite remains are found at the base of the Lower Cretaceous strata, and there are no fossils of marine fauna in younger rocks (Repin et al., 2007). Jurassic and Berriasian–Hauterivian deposits are unconformably overlain by Barremian–Albian coal‐bearing, volcanic‐sedimentary rocks and basalts (Ershova et al., 2022; Shkarubo et al., 2017). The volcanic‐sedimentary sequence contains imprints of leaves, carbonatised and silicified wood remains and myospores, which allow dating of the sequence to the Barremian, Aptian and Albian.…”
Section: Geological Settingsmentioning
confidence: 99%